Fístula cardiocutânea com corpo estranho em ventrículo direito: complicação tardia e rara do uso de cateter venoso central de inserção periférica - Stéfanie Dias Rodrigues; Nabel Anderson de Lencaster Saldanha da Cunha; Genivalda de Medeiros Barros; Gotardo Duarte Dumaresq; Laura Alencar Pinto (Sociedade Brasileira de Pediatria, 2024)
INTRODUCTION: Foreign bodies in the heart are rare and a small number of cases are reported about this event. There are different mechanisms by which objects can reach a cardiac chamber axnd cause myoxcardial perforation, so an individualized diagnostic approach must be taken to define the management of these cases. OBJECTIVES: To report the case of a five-year-old pediatric patient with a cardiocutaneous fistula caused by a caused by a fragment of a peripherally inserted central catheter (PICC) in the right ventricle (RV). CASE REPORT: A 5-year-old male patient with a history of blunt chest trauma due to a fall from his own height a year ago, followd by a chest wall abscess, after 20 days. After drainage, a recurrent outflow of serous and bloody secretion from the lesion persisted. Eleven months after the event, the patient started to present daily high fever, local hyperemia, and increased drainage secretion. The diagnostic investigation showed an Intracardiac foreign body with the presence of a cardiocutaneous fistula. Due to the past of peripherally inserted central catheter (PICC) during the neonatal period, it is believed that the catheter fragmented and remained asymptomatically lodged in the RV, with exteriorization through the skin after 5 years. CONCLUSION: Cardiocutaneous fistula caused by a foreign body in the heart is a rare event and may be caused by fracture and migration of a PICC. The diagnosis must be made through a detailed clinical history, aligned with adequate imaging exams.